PENERAPAN TEKNIK MOTION GRAPHIC PADA DIGITAL OUT OF HOME ADVERTISING UNTUK TEMPLATE VIDEOTRON - Hafidh Rezha Maulana; Ema Utami; Hanif Al Fatta (Universitas Janabadra, 2018)
Outdoor billboard is media with a variety of shapes and styles which are widely used for commercial purposes. Basically, people still need outdoor space media/advertising/billboards and the other kinds of information on the existence of the product or service to meet the needs of life. Digital advertising industry will continue to increase its development until the next five years. Because of the market share of the industry is more wide open with increasingly advanced digital era. Motion graphics is currently widely used both in the world of film, television, and advertising. This study aims to determine the application template after effects using motion graphic techniques in disseminating information on DOOH Advertising is Videotron. The object of this study aimed to Java Videotron with video content Dimas Diajeng Bantul 2016, with a duration of 30 seconds. The method used to analyze this study is Reverse Engineering and Forward Engineering. This research resulted in the output of the template on DOOH the 30-second video that can be used continuously and modified by a variety of multimedia elements with easy navigation. Digest Thesis contains what and why research is done, how to do, and what important results obtained from research. The first paragraph in essence contains the title of the research, research objectives, constraints and variables of research, as well as the methods of analysis used in the study. The second paragraph contains a summary of the results of research and discussion. The third paragraph expresses the conclusions of the study.Keywords : motion graphic, digital out of home advertising, template, videotron